Hybridization and restricted gene flow between native and introduced stocks of Alpine whitefish (Coregonus sp.) across multiple environments - Winkler, Kathrin A (Blackwell Publishing Ltd, 2011)
Translocations of Baltic whitefish (Coregonus sp.) into Austrian Alpine lakes have created ‘artificial hybrid zones’, threatening the genetic integrity of native lineages. We evaluate the genetic structure of Coregonus in Austrian lakes and characterize hybridization and introgression between native and introduced lineages. Fifteen populations (N= 747) were assessed for allelic variation at eight microsatellite loci and a reduced set (N= 253) for variation across two mtDNA genes (cyt b and NADH-3). Bayesian approaches were used to estimate individual admixture proportions (q-values) and classify genotypes as native, introduced or hybrids. q-value distributions varied among populations highlighting differential hybridization and introgression histories. Many lakes revealed a clear distinction between native and introduced genotypes despite hybridization, whereas some locations revealed hybrid swarms. Genetic structure among lakes was congruent with morphological divergence and novelty raising speculation of multiple taxa, including a population south of the Alps, outside the putative native range of Coregonus. Although statistically congruent with inferences based on nuclear markers, mitochondrial haplotype data was not diagnostic with respect to native and non-native lineages, supporting that the Alpine region was colonized post-glacially by an admixture of mtDNA lineages, which coalesce >1 Ma. Mechanisms promoting or eroding lineage isolation are discussed, as well as a high potential to conserve native Alpine lineages despite the extensive historical use of introduced Baltic stocks.